Assessment of China's contributions to the Regional Network for Asian Schistosomiasis and Other Helminth Zoonoses: a questionnaire survey - Hong-Mei Li; Ying-Jun Qian; Kun Yang; Wei Ding; Lu-Lu Huang; Xue-Jiao Ma; Lei Duan; Duo-Quan Wang; Ya-Yi Guan; Ning Xiao; Xiao-Nong Zhou (BMC, 2021)
Abstract Background The Regional Network for Asian Schistosomiasis and Other Helminth Zoonoses (RNAS+) was established in 1998, which has developed close partnerships with Asian countries endemic for schistosomiasis and other helminthiasis in Asia. RNAS+ has provided an ideal regional platform for policy-makers, practitioners and researchers on the prevention, control and research of parasitic diseases in Asian countries. China, one of the initiating countries, has provided significant technical and financial support to the regional network. However, its roles and contributions have not been explored so far. The purpose of this study was to assess China's contributions on the supporting of RNAS+ development. Methods An assessment research framework was developed to evaluate China's contributions to RNAS+ in four aspects, including capacity building, funding support, coordination, and cooperation. An anonymous web-based questionnaire was designed to acquire respondents' basic information, and information on China's contributions, challenges and recommendations for RNAS+development. Each participant scored from 0 to 10 to assess China's contribution: "0" represents no contribution, and "10" represents 100% contribution. Participants who included their e-mail address in the 2017-2019 RNAS+ annual workshops were invited to participate in the assessment. Results Of 71 participants enrolled, 41 responded to the survey. 37 (37/41, 90.24%) of them were from RNAS+ member countries, while the other 4 (4/41, 9.76%) were international observers. Most of the respondents (38/41, 92.68%) were familiar with RNAS+. Respondents reported that China's contributions mainly focused on improving capacity building, providing funding support, coordination responsibility, and joint application of cooperation programs on RNAS+ development. The average scores of China's contributions in the above four fields were 8.92, 8.64, 8.75, and 8.67, respectively, with an overall assessment score of 8.81 (10 for a maximum score). The challenge of RNAS+ included the lack of sustainable funding, skills, etc. and most participants expressed their continual need of China's support. Conclusions This survey showed that China has played an important role in the development of RNAS+ since its establishment. This network-type organization for disease control and research can yet be regarded as a great potential pattern for China to enhance regional cooperation. These findings can be used to promote future cooperation between China and other RNAS+ member countries.